2003
DOI: 10.1007/s00424-003-1126-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α induces unsynchronized intracellular calcium oscillations in monolayers of gap junctionally coupled NRK fibroblasts

Abstract: We investigated the intracellular calcium oscillations induced by prostaglandin F2alpha (PGF2alpha) in individual cells of confluent, gap junction-coupled monolayers of normal rat kidney (NRK) fibroblasts. PGF2alpha (1000 nM) induced oscillations in more than 90% of the cells in the monolayer, but the frequency of these oscillations was highly variable between individual cells (0.2-1.4 min(-1)). The initial calcium peak resulted from calcium release from IP3-sensitive stores, while subsequent calcium transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 53 publications
6
28
0
1
Order By: Relevance
“…Repetitive addition of either the CM of transformed NRK cells or TransX showed no homologous desensitization, in agreement with the finding that PGF 2␣ only partially desensitizes its natural G protein-coupled receptor (10). The binding of PGF 2␣ to this FP receptor previously was shown to result in increased intracellular IP 3 and Ca 2ϩ levels (23), and we recently demonstrated that PGF 2␣ can induce intracellular Ca 2ϩ oscillations in NRK cells cultured in quiescent monolayers (13). These oscillations resulted from an intricate interplay between Ca 2ϩ release from internal stores and Ca 2ϩ influx over the plasma membrane and were not synchronized in spite of gap junctional coupling of the NRK cells in such monolayers.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Repetitive addition of either the CM of transformed NRK cells or TransX showed no homologous desensitization, in agreement with the finding that PGF 2␣ only partially desensitizes its natural G protein-coupled receptor (10). The binding of PGF 2␣ to this FP receptor previously was shown to result in increased intracellular IP 3 and Ca 2ϩ levels (23), and we recently demonstrated that PGF 2␣ can induce intracellular Ca 2ϩ oscillations in NRK cells cultured in quiescent monolayers (13). These oscillations resulted from an intricate interplay between Ca 2ϩ release from internal stores and Ca 2ϩ influx over the plasma membrane and were not synchronized in spite of gap junctional coupling of the NRK cells in such monolayers.…”
Section: Discussionsupporting
confidence: 86%
“…The fragmentation peaks resulted from the sequential losses of water (from m/z 377.3 to m/z 359.3 to m/z 341.3) and both water and carboxyl (from m/z 377.3 to m/z 315.3) from the parent compound. These results demonstrate that TransX contains PGF 2␣ and that the depolarizing activity of TransX can be ascribed to this prostaglandin (13).…”
Section: Growth State-dependent Membrane Potential Of Nrk Cellsmentioning
confidence: 56%
See 2 more Smart Citations
“…[i] oscillations have been shown to be synchronised between fibroblasts that intrinsically oscillate with similar frequencies (Harks et al, 2003).…”
Section: +mentioning
confidence: 99%